Persepsi Konsumen terhadap Buah Jeruk Lokal dan Jeruk Impor di Kota Denpasar - SIMARMATA, MONICA INDAH LESTARI; SUDARMA, I MADE; ANGGRENI, IGAA LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Consumer Perception of Local and Imported Orange in Denpasar The purpose of this study was to determine the level of consumer perceptions of local citrus fruits and imported oranges in Denpasar City and to find out whether there were differences in consumer perceptions of local citrus fruits and imported oranges in Denpasar City. This research was conducted in Denpasar City, namely in the traditional markets and modern markets that have been determined. The population in this study were consumers who bought and consumed local citrus fruits and imported oranges using the accidental sampling method, which was accidentally taking samples at the research location while buying or having consumed local citrus fruits and imported oranges, the number of respondents was 40. Data collection was used in This study uses interview methods, namely structured interviews and in-depth interviews. The data analysis used in this study is descriptive analysis and Mann-Whitney test analysis (U Test) using SPSS 20. Oranges are one of the most consumed fruits by the community, because besides being easily accessible to oranges, they also have high vitamin C content. The people of Denpasar City are one of the consumers who buy and consume local citrus fruits and imported oranges, because besides being consumed citrus fruit is used as a complementary means of religious ceremonies for Hindus on holidays. Various types of oranges sold on the market make consumers have to make decisions about the type of oranges that will be bought. The level of consumer perceptions of imported oranges is higher than the level of consumer perception of local oranges. Indicators of taste, color, texture, aroma, availability, and price determine the different perceptions of local jeurk and imported oranges in Denpasar City. Based on the results of analysis, consumers consider that the quality of imported oranges is better than local oranges. Researcher's suggestion is that there is a need for firmness from the government regarding the holding of imported fruit restrictions so as not to suppress similar products produced domestically.